A systematic review of the academic achievement of primary and secondary school-aged students with developmental language disorder. (June 2022) - Ziegenfusz, Shaun; Paynter, Jessica; Flückiger, Beverley; Westerveld, Marleen F
Background and aims: The ability to communicate is a fundamental skill required to participate in school. Students with Developmental Language Disorder (DLD) have persistent and significant language difficulties that impact daily functioning. However, the impact of DLD on the academic achievement of primary and secondary school-aged students has received limited attention. Methods: A systematic review of the empirical research published between 2008 and 2020 was undertaken to identify studies that have examined the academic achievement of school-aged students with DLD within curriculum areas. A total of 44 studies were identified that met inclusion criteria for review. Results: Students with DLD demonstrated difficulties with academic achievement across all measured curriculum areas compared to their typically developing peers. Most studies focused on literacy skills, including reading, spelling, writing and narratives. Conclusions and implications: The performance of students with DLD was heterogeneous with individual students demonstrating relative strengths in some areas of academic achievement. The implications of these results for educational practices and future research are discussed.